Pengukuran Ergonomi Sikap Kerja Pengrajin Sulam Lampung dengan Metode RULA & REBA dan Rekomendasi Perbaikan - Sari, Indah Purnama; Suwarni, Putri Endah; Sundari, Susanti; Buari, Jevri; Prasetyo, Agung Dwi (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
The ergonomic assessment of the working posture of traditional embroidery artisans in Lampung is necessary to uncover their working conditions and their impact on health, with the main complaint being significant musculoskeletal disorders. This study aims to identify the ergonomic risk levels of the artisans and provide recommendations for corrective measures. The research utilized the Nordic Body Map questionnaire to identify the body areas with the highest complaints, while ergonomic analysis was conducted using the Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) methods. The findings revealed that the back (100%), buttocks (80%), lower neck (80%), right shoulder (80%), waist (70%), and upper neck (70%) were the areas with the highest complaints. The RULA score was 6 for embroidery and pattern-making activities, indicating that corrective actions are needed in the near future. The REBA scores were 5 for embroidery and 6 for pattern-making, emphasizing the urgency for improvement. Immediate corrective actions, such as the provision or replacement of ergonomic embroidery frames or tables, are required to reduce injury risks and enhance the occupational health of the artisans. Keywords: Artisans, Ergonomic, Nordic Body Map, REBA, RULA